Daya Hambat Jamur Endofitik Terhadap Fusarium oxysporum f.sp. capsici Penyabab Layu Fusarium Pada Tanaman Cabai (Capsicum frutescens L.) - Polhaupessy, Vanda C; Taribuka, Johanna; Talahaturuson, Abraham (Universitas Pattimura, 2025)
This research aims to obtain endophytic fungi from healthy chili plants (Capsicum frutescens L.) and test the inhibitory power of endophytic fungi, which are thought to have the potential to control the pathogen that causes fusarium wilt disease (Fusarium oxysporum f.sp. capsici) in chili plants (Capsicum frutescens L.). The exploration results obtained five genera of endophytic fungi from different plant parts and in different villages and hamlets, including Colletotrichum sp.TWtc, Rhizoconia sp.TWdc, Trichoderma sp.TKac, Penicillium sp.TKbc, and Aspergilus sp.TObtc, The percentage of inhibitory power of the five endophytic fungal genera against the pathogenic fungus F.oxysporum f.sp capsici is as follows: Trichoderma sp.TKac, which is 85.29%, followed by the isolate Rhizoctonia sp.TWdc, which is 62.14%, isolates Penicillium sp. TKbc was 61.31%, Colletotrichum sp.TWtc isolate was 60.27% and the lowest inhibitory power was Aspergillus sp.TObtc isolates were 46.42%. Conclusion: The endophytic fungus Trichoderma sp. TKac has the highest inhibitory ability against the pathogenic fungus F.oxysporum f.sp.capsici, so it can be used as a biological control agent.